This printout should have 20 questions.
Multiplechoice questions may continue on
the next column or page – ﬁnd all choices
before answering.
001 10.0 points
To apply the root test to an inﬁnite series
k
a
k
, the value of
ρ = lim
k →∞
a
k

1/k
has to be determined.
Compute the value of ρ for the series
∞
k =1
2
k
k
(ln k + 6)
k
.
1. ρ = 2
2. ρ = 6
3. ρ = ∞
4. ρ = 0 correct
5. ρ = 12
Explanation:
For the given series
(a
k
)
1/k
= 2
1/k
_
lnk + 6
k
_
= 2
1/k
_
lnk
k
+
6
k
_
.
But
2
1/k
−→ 1,
ln k
k
−→ 0
as k → ∞. Consequently,
ρ = 0 .
002 10.0 points
Which, if any, of the following series converge?
(A)
∞
n=5
_
2
3
_
n
(B)
∞
k =2
1
k ln k + 3
1. B but not A
2. A but not B correct
3. neither A nor B
4. A and B
Explanation:
(A) Since
∞
n=3
_
2
3
_
n
is a geometric series with common ratio r =
2
3
< 1, the series
converges .
(B) Since
lim
k →∞
k ln k
k lnk + 3
= 1 ,
the series
∞
k =2
1
k ln k + 3
converges if the series
∞
k =2
1
k ln k
converges.
But by the Integral Test with
f(x) =
1
x lnx
,
the series
∞
k =2
1
k ln k
Version 046 – L EXAM 3 – guntel – (55200) 2
converges if the improper integral
_
∞
2
f(x) dx =
_
∞
2
1
x lnx
dx
converges, i.e., if
lim
t →∞
_
t
2
1
x lnx
dx
exists. We use the substition
u = ln x .
For then
du =
1
x
dx ,
and so
_
t
2
1
x lnx
dx =
_
lnt
ln 2
1
u
du
=
_
lnu
_
ln t
ln 2
= ln(lnt) −ln(ln2) .
Since
lim
t →∞
ln(lnt) = ∞,
the given series thus
diverges .
003 10.0 points
Determine whether the series
∞
n=1
cos
2
n
n
2
+ 4
converges or diverges.
1. series is convergent correct
2. series is divergent
Explanation:
Note ﬁrst that the inequalities
0 <
cos
2
n
n
2
+ 4
≤
1
n
2
+ 4
≤
1
n
2
hold for all n ≥ 1. On the other hand, by the
pseries test the series
∞
n=1
1
n
2
is convergent since p = 2 > 1. Thus, by the
comparison test, the given
series is convergent .
004 10.0 points
Determine whether the inﬁnite series
∞
n=1
ln
_
2n
3n + 2
_
is convergent or divergent, and if convergent,
ﬁnd its sum.
1. diverges correct
2. converges with sum = ln
_
3
2
_
3. converges with sum = ln
_
2
3
_
4. converges with sum = ln
_
2
5
_
5. converges with sum = ln
_
5
2
_
Explanation:
An inﬁnite series
a
n
diverges when
lim
n→∞
a
n
= 0 .
For the given series
a
n
= ln
_
2n
3n + 2
_
.
But
lim
n→∞
_
2n
3n + 2
_
= lim
n→∞
_
2
3 +
2
n
_
=
2
3
,
Version 046 – L EXAM 3 – guntel – (55200) 3
so
lim
n→∞
ln
_
2n
3n + 2
_
= ln
2
3
= 0 .
Consequently, the given inﬁnite series
diverges .
005 10.0 points
Determine whether the series
3
5
−
4
6
+
5
7
−
6
8
+
7
9
−. . .
is absolutely convergent, conditionally con
vergent or divergent.
1. conditionally convergent
2. divergent correct
3. absolutely convergent
Explanation:
In summation notation,
3
5
−
4
6
+
5
7
−
6
8
+
7
9
−. . . =
∞
n=3
a
n
,
with a
n
given by
a
n
= (−1)
n
n
n + 2
.
However,
lim
n→∞
n
n + 2
= 1 ,
so that as n → ∞, a
n
oscillates between val
ues approaching 1 and −1. In particular,
therefore,
lim
n→∞
a
n
= 0 .
Consequently, by the Divergence Test, the
series is divergent .
006 10.0 points
Determine whether the following series
(A)
∞
n=1
3 ln(4n)
n
2
,
(B)
∞
n=1
1 + sin(4n)
n
2
+ 1
converge or diverge.
1. both series diverge
2. A diverges, B converges
3. A converges, B diverges
4. both series converge correct
Explanation:
(A) The function
f(x) =
3 ln 4x
x
2
is continous and positive on
_
1
2
, ∞
_
; in addi
tion, since
f
′
(x) = 3
_
1 −2 ln 4x
x
3
_
< 0
on
_
1
2
, ∞
_
, f is also decreasing on this inter
val. This suggests applying the Integral Test.
Now, after Integration by Parts, we see that
_
t
1
f(x) dx = 3
_
−
ln(4x)
x
−
1
x
_
t
1
,
and so
_
∞
1
f(x) dx = 3(1 + ln 4) .
The Integral Test thus ensures that series (A)
converges .
(B) Note ﬁrst that the inequalities
0 ≤
1 + sin(4n)
n
2
+ 1
≤
2
n
2
+ 1
≤
2
n
2
Version 046 – L EXAM 3 – guntel – (55200) 4
hold for all n ≥ 1. On the other hand, by the
pseries test the series
∞
n=1
1
n
2
is convergent since p = 2 > 1. Thus, by the
comparison test, series (B)
converges .
007 10.0 points
Determine whether the inﬁnite series
∞
n=1
3
n
−2
n
5
n
converges or diverges, and if it converges, ﬁnd
its sum.
1. converges with sum = 1
2. series diverges
3. converges with sum =
2
3
4. converges with sum =
5
6
correct
5. converges with sum =
1
4
6. converges with sum =
1
2
Explanation:
An inﬁnite geometric series
∞
n=1
a r
n−1
(i) converges when r < 1 and has
sum =
a
1 −r
,
while it
(ii) diverges when r ≥ 1 .
Now
∞
n=1
3
n
5
n
=
∞
n=1
3
5
_
3
5
_
n−1
is a geometric series with a = r =
3
5
< 1.
Thus it converges with
sum =
3
2
,
while
∞
n=1
2
n
5
n
=
∞
n=1
2
5
_
2
5
_
n−1
is a geometric series with a = r =
2
5
< 1.
Thus it too converges, and it has
sum =
2
3
.
Consequently, being the diﬀerence of two con
vergent series, the given series
converges with sum =
3
2
−
2
3
=
5
6
.
008 10.0 points
Determine whether the series
∞
n=1
(−1)
n+1
e
1/n
7n
is absolutely convergent, conditionally con
vergent or divergent.
1. absolutely convergent
2. conditionally convergent correct
3. divergent
Explanation:
Since
∞
n=1
(−1)
n+1
e
1/n
7n
= −
1
7
∞
n=1
(−1)
n
e
1/n
n
,
we have to decide if the series
∞
n=1
(−1)
n
e
1/n
n
Version 046 – L EXAM 3 – guntel – (55200) 5
is absolutely convergent, conditionally con
vergent, or divergent.
First we check for absolute convergence.
Now, since e
1/n
≥ 1 for all n ≥ 1,
e
1/n
7n
≥
1
7n
> 0 .
But by the pseries test with p = 1, the series
∞
n=1
1
7n
diverges, and so by the Comparison Test, the
series
∞
n=1
e
1/n
7n
too diverges; in other words, the given series
is not absolutely convergent.
To check for conditional convergence, con
sider the series
∞
n=1
(−1)
n
f(n)
where
f(x) =
e
1/x
7x
.
Then f(x) > 0 on (0, ∞). On the other hand,
f
′
(x) = −
1
7x
3
e
1/x
−
e
1/x
7x
2
= −e
1/x
_
1 + x
7x
3
_
.
Thus f
′
(x) < 0 on (0, ∞), so f(n) > f(n+1)
for all n. Finally, since
lim
x→∞
e
1/x
= 1 ,
we see that f(n) → 0 as n → ∞. By the
Alternating Series Test, therefore, the series
∞
n=1
(−1)
n
f(n)
is convergent.
Consequently, the given series is
conditionally convergent .
keywords:
009 10.0 points
Which one of the following properties does
the series
∞
n=1
(−1)
n−1
3n
2
+ 4
2
n
have?
1. divergent
2. conditionally convergent
3. absolutely convergent correct
Explanation:
The given series has the form
∞
n=1
(−1)
n−1
b
n
, b
n
=
3n
2
+ 4
2
n
of an alternating series. But the denominator
is increasing very fast, so ﬁrst let’s check if
the series is absolutely convergent rather than
simply conditionally convergent. We use the
Ratio test, for then
¸
¸
¸
(−1)
n
b
n+1
(−1)
n−1
b
n
¸
¸
¸ =
b
n+1
b
n
=
1
2
3(n + 1)
2
+ 4
3n
2
+ 4
.
But
3(n + 1)
2
+ 4
3n
2
+ 4
=
3n
2
+ 6n + 7
3n
2
+ 4
−→ 1
as n → ∞. Thus
lim
n→∞
¸
¸
¸
(−1)
n
b
n+1
(−1)
n−1
b
n
¸
¸
¸ =
1
2
< 1 .
Consequently, by the Ratio test, the given
series is
absolutely convergent .
010 10.0 points
Version 046 – L EXAM 3 – guntel – (55200) 6
Determine whether the series
∞
n=0
(−3)
n
(2n)!
is absolutely convergent, conditionally con
vergent, or divergent.
1. conditionally convergent
2. absolutely convergent correct
3. divergent
Explanation:
We use the Ratio Test with
a
n
=
(−3)
n
(2n)!
.
For then
¸
¸
¸
a
n+1
a
n
¸
¸
¸ =
¸
¸
¸
(−3)
n+1
(2n + 2)!
(2n)!
(−3)
n
¸
¸
¸
=
¸
¸
¸
(−3)
n+1
(2n + 2)!
(2n)!
(−3)
n
¸
¸
¸=
¸
¸
¸
−3
(2n + 1)(2n + 2)
¸
¸
¸ .
Thus
lim
n→∞
¸
¸
¸
a
n+1
a
n
¸
¸
¸
= lim
n→∞
3
(2n + 1)(2n + 2)
= 0 < 1 .
Consequently, the
series is absolutely convergent .
011 10.0 points
Which one of the following properties does
the series
∞
n=1
(−1)
n
3
_
tan
−1
n
_
5
have?
1. absolutely convergent
2. conditionally convergent
3. divergent correct
Explanation:
Since
0 < tan
−1
x <
π
2
, 0 < x < ∞,
while
lim
x→∞
tan
−1
x =
π
2
,
we see that
lim
n→∞
1
(tan
−1
n)
5
=
_
2
π
_
5
= 0 .
But then it follows that
(−1)
n
3
(tan
−1
n)
5
→ 0
as n →∞because the values oscillate without
approaching 0.
The Divergence test thus says that the
given series is
divergent .
012 10.0 points
Find the interval of convergence of the se
ries
∞
n=1
(−1)
n
x
n
2n
2
+ 1
.
1. converges only at x = 0
2. interval of cgce = (−2, 1]
3. interval of cgce = (−1, 1]
4. interval of cgce = [−1, 1)
5. interval of cgce = [−1, 1] correct
6. interval of cgce = [−2, 1]
Explanation:
Version 046 – L EXAM 3 – guntel – (55200) 7
When
a
n
= (−1)
n
x
n
2n
2
+ 1
,
then
¸
¸
¸
¸
a
n+1
a
n
¸
¸
¸
¸
=
¸
¸
¸
¸
−
x
n+1
2(n + 1)
2
+ 1
2n
2
+ 1
x
n
¸
¸
¸
¸
= x
_
2n
2
+ 1
2(n + 1)
2
+ 1
_
.
But
2(n + 1)
2
+ 1 = 2n
2
+ 4n + 3 ,
while
lim
n→∞
2n
2
+ 1
2n
2
+ 4n + 3
= 1 .
Thus
lim
n→∞
¸
¸
¸
¸
a
n+1
a
n
¸
¸
¸
¸
= x .
By the Ratio Test, therefore, the given series
(i) converges when x < 1,
(ii) diverges when x > 1.
We have still to check what happens at the
endpoints x = ±1. At x = −1 the series
becomes
(∗)
∞
n=1
1
2n
2
+ 1
.
Applying the Integral Test with
f(x) =
1
2x
2
+ 1
we see that f is continuous, positive, and de
creasing on [1, ∞); in addition,the improper
integral
I =
_
∞
1
f(x) dx
converges, so the inﬁnite series (∗) converges
also.
On the other hand, at x = 1, the series
becomes
(‡)
∞
n=1
(−1)
n
2n
2
+ 1
.
which is an alternating series
∞
n=1
(−1)
n
a
n
, a
n
= f(x)
with
f(x) =
1
2x
2
+ 1
the same continuous, positive and decreasing
function as before. As
lim
x→∞
f(x) = lim
x→∞
1
2x + 1
= 0 ,
the Alternating Series Test thus ensures that
(‡) too converges.
Consequently, the
interval of convergence = [−1, 1] .
013 10.0 points
Determine the interval of convergence of
the series
∞
k =1
(−1)
k
1
k 2
k
(2x + 1)
k
.
1. interval convergence = (−∞, ∞)
2. interval convergence =
_
−
3
2
,
1
2
_
3. converges only at x = −
1
2
4. interval convergence =
_
−
3
2
,
1
2
_
5. interval convergence =
_
−
3
2
,
1
2
_
cor
rect
6. interval convergence =
_
−
3
2
,
1
2
_
Explanation:
∞
k =1
c
k
_
x +
1
2
_
k
, c
k
=
(−1)
k
k
.
Version 046 – L EXAM 3 – guntel – (55200) 8
But then
lim
k →∞
¸
¸
¸
c
k+1
c
k
¸
¸
¸ = lim
k →∞
k
k + 1
= 1 .
By the Ratio Test, therefore, the series
(i) converges when x+
1
2
 < 1,
(ii) diverges when x+
1
2
 > 1.
Now at the point x+
1
2
= 1, the series reduces
to
∞
k =1
(−1)
k
k
,
while at x+
1
2
= −1, it reduces to
∞
k =1
1
k
.
In the ﬁrst case the series converges by the
Alternating Series Test, while in the second
it diverges by the pSeries Test with p = 1.
Consequently, the series has
interval of convergence =
_
−
3
2
,
1
2
_
.
014 10.0 points
If the series
∞
n=0
c
n
x
n
converges when x = −4 and diverges when
x = 7, which of the following series must
converge without further restrictions on {c
n
}?
A.
∞
n=0
c
n
(−2)
n
B.
∞
n=0
c
n
4
n
1. A only correct
2. both of them
3. B only
4. neither of them
Explanation:
A. The interval of convergence of series
∞
n=0
c
n
x
n
contains (−4, 4). Since x = −2 belongs to
this interval, the series
n=0
c
n
(−2)
n
converges also.
B. The series
∞
n=0
c
n
4
n
need not converge even though
∞
n=0
(−1)
n
c
n
4
n
converges.
015 10.0 points
Find a power series representation for the
function
f(z) =
z
9z + 1
.
1. f(z) =
∞
n=0
(−1)
n
3
n
z
n
2. f(z) =
∞
n=0
3
2n
z
n+1
3. f(z) =
∞
n=0
(−1)
n
3
n
z
n+1
4. f(z) =
∞
n=0
(−1)
n
3
2n
z
n+1
correct
5. f(z) =
∞
n=0
3
2n
z
n
6. f(z) =
∞
n=0
3
n
z
n
Version 046 – L EXAM 3 – guntel – (55200) 9
Explanation:
After simpliﬁcation,
f(z) =
z
9z + 1
=
z
1 −(−9z)
.
On the other hand,
1
1 −x
=
∞
n=0
x
n
.
Thus
f(z) = z
_
∞
n=0
(−9z)
n
_
= z
_
∞
n=0
(−1)
n
3
2n
z
n
_
.
Consequently,
f(z) =
∞
n=0
(−1)
n
3
2n
z
n+1
.
keywords:
016 10.0 points
Find a power series representation for the
function
f(x) = tan
−1
(3x) .
1. f(x) =
∞
n=0
1
2n + 1
x
2n+1
2. f(x) =
∞
n=0
(−1)
n
1
2n + 1
x
2n+1
3. f(x) =
∞
n=0
(−1)
n
3
2n
2n + 1
x
2n
4. f(x) =
∞
n=0
3
2n+1
2n + 1
x
2n+1
5. f(x) =
∞
n=0
1
2n + 1
x
2n
6. f(x) =
∞
n=0
(−1)
n
3
2n+1
2n + 1
x
2n+1
correct
Explanation:
We know that
tan
−1
x =
_
x
0
1
1 + t
2
dt .
On the other hand,
1
1 −x
= 1 + x + x
2
+ . . .
on the interval (−1, 1). Replacing x by −x
2
we thus see that
1
1 + x
2
= 1 −x
2
+ x
4
−x
6
+ . . .
=
∞
n=0
(−1)
n
x
2n
on (−1, 1). But then
f(x) =
_
x
0
_
∞
n=0
(−1)
n
t
2n
_
dt
=
∞
n=0
_
(−1)
n
_
x
0
t
2n
dt
_
=
∞
n=0
(−1)
n
2n + 1
x
2n+1
on (−1, 1). Consequently,
tan
−1
(3x) =
∞
n=0
(−1)
n
3
2n+1
2n + 1
x
2n+1
is a power series representation for tan
−1
(3x)
on
_
−
1
3
,
1
3
_
.
017 10.0 points
Find a power series representation centered
at the origin for the function
f(y) =
y
3
(4 −y)
2
.
Version 046 – L EXAM 3 – guntel – (55200) 10
1. f(y) =
∞
n=3
n −2
4
n−1
y
n
correct
2. f(y) =
∞
n=2
n −1
4
n
y
n
3. f(y) =
∞
n=3
1
4
n−3
y
n
4. f(y) =
∞
n=2
1
4
n−1
y
n
5. f(y) =
∞
n=3
n
4
n
y
n
Explanation:
By the known result for geometric series,
1
4 −y
=
1
4
_
1 −
y
4
_
=
1
4
∞
n=0
_
y
4
_
n
=
∞
n=0
1
4
n+1
y
n
.
This series converges on (−4, 4).
On the other hand,
1
(4 −y)
2
=
d
dy
_
1
4 −y
_
,
and so on (−4, 4),
1
(4 −y)
2
=
d
dy
_
∞
n=0
y
n
4
n+1
_
=
∞
n=1
n
4
n+1
y
n−1
=
∞
n=0
n + 1
4
n+2
y
n
.
Thus
f(y) = y
3
∞
n=0
n + 1
4
n+2
y
n
=
∞
n=0
n + 1
4
n+2
y
n+3
.
Consequently,
f(y) =
∞
n=3
n −2
4
n−1
y
n
.
018 10.0 points
Find the degree 2 Taylor polynomial of f
centered at x = 3 when
f(x) = 5x lnx .
1. 15 ln 3 + 5 ln3(x −3) +
5
6
(x −3)
2
2. 15 ln 3 + 5(ln3 + 1)(x − 3) +
5
6
(x − 3)
2
correct
3. 15 + 5(ln3 + 1)(x −3) +
5
6
(x −3)
2
4. 15 ln3 +5(ln3 +1)(x −3) +
5
3
(x −3)
2
5. 15 + 3 ln5(x −3) +
5
6
(x −3)
2
6. 15 + 5 ln3(x −3) +
5
3
(x −3)
2
Explanation:
The degree 2 Taylor polynomial of f cen
tered at x = 3 is given by
T
2
(x) = f(3) + f
′
(3)(x −3)
+
1
2!
f
′′
(3)(x −3)
2
.
When f(x) = 5x lnx, therefore,
f
′
(x) = 5 lnx + 5, f
′′
(x) =
5
x
.
But when f(3) = 15 ln3,
f
′
(3) = 5(ln3 + 1) , f
′′
(3) =
5
3
.
Consequently, the degree 2 Taylor polynomial
centered at x = 3 of f is
15 ln 3 + 5(ln3 + 1)(x −3) +
5
6
(x −3)
2
.
019 10.0 points
Version 046 – L EXAM 3 – guntel – (55200) 11
Find the coeﬃcient of x
6
in the Taylor se
ries expansion centered at the origin for the
function
f(x) = 7 + 3 sin(x
2
).
1. coeﬃcient of x
6
= −
7
6
2. coeﬃcient of x
6
=
1
2
3. coeﬃcient of x
6
= −
1
2
correct
4. coeﬃcient of x
6
= −3
5. coeﬃcient of x
6
= 3
Explanation:
The Taylor series expansion for
f(x) = 7 + 3 sin(x
2
)
can be determined from ﬁrst principles by
computing all the various derivatives of f(x),
but this is very lengthy and algebraically te
dious. It is much simpler to start with the
known expansion
7 + 3 sinx = 7 + 3
_
x −
x
3
3!
+
x
5
5!
+ . . .
_
which holds everywhere on (−∞, ∞). For
then the Taylor series expansion centered at
the origin for f(x) is obtained on replacing x
by x
2
since any convergent series expansion in
powers of x must be the Taylor series centered
at the origin. Thus
f(x) = 7 + 3
_
x
2
−
x
6
3!
+
x
10
5!
+ . . .
_
and this too holds everywhere on (−∞, ∞).
By inspection, therefore,
coeﬃcient of x
6
= −
1
2
.
keywords: Taylor series, Taylor coeﬃcient,
sine function,
020 10.0 points
Use the degree 2 Taylor polynomial cen
tered at the origin for f to estimate the inte
gral
I =
_
1
0
f(x) dx
when
f(x) = e
−x
2
/2
.
1. I ≈
1
3
2. I ≈ 1
3. I ≈
1
2
4. I ≈
5
6
correct
5. I ≈
2
3
Explanation:
When f(x) = e
−x
2
/2
, we see that
f
′
(x) = −xe
−x
2
/2
,
while
f
′′
(x) = −e
−x
2
/2
+ x
2
e
−x
2
/2
.
In this case,
f(0) = 1, f
′
(0) = 0, f
′′
(0) = −1 .
Thus the degree 2 Taylor polynomial for f
centered at the origin is
T
2
(x) = 1 −
1
2
x
2
.
But then
I ≈
_
1
0
T
2
(x) dx =
_
1
0
_
1 −
1
2
x
2
_
dx .
Consequently,
I ≈
_
x −
1
6
x
3
_
1
0
=
5
6
.